C# 2008 For Dummies - Chuck Sphar and Stephen Randy Davis (Wiley India, 2008)
This plain-English guide to programming with C# can have you creating your first console application before you finish Part I. In fact, the basic template you create at that point will be the foundation of many other apps as you move through the book. Along the way you ll get the scoop on organizing your data, object-oriented programming (also known as OOP), and a great LINQ-related feature called delegates and events.· Creating Your First C# Console Application · Living with Variability - Declaring Value-Type Variables · Smooth Operators · Getting into the Program Flow · Lining Up Your Ducks with Collections · Pulling Strings · Showing Some Class · We Have Our Methods · Let Me Say This about this · Object-Oriented Programming - What s It All About? · Holding a Class Responsible · Inheritance - Is That All I Get? · Poly-what-ism? · Interfacing with the Interface · Delegating Those Important Events · Mary Had a Little Lambda Expression · LINQing Up with Query Expressions ·